New Insights in Diagnosing and Risk-Stratifying Pancreatic Cystic Neoplasms and IPMN - Pollini, Tommaso; Maker, Ajay V. (Digestive Disease Interventions, 2025)
Pancreatic cystic neoplasms (PCN) comprise a diverse group of lesions with variable malignant potential, requiring accurate diagnosis and risk stratification for appropriate management. Distinguishing mucinous cysts, including intraductal papillary mucinous neoplasms (IPMN) and mucinous cystic neoplasms (MCN), from benign nonmucinous lesions such as serous cystadenomas (SCA) is essential due to their risk of progression to invasive carcinoma. Importantly, IPMN and MCN represent the only radiologically detectable precursors to pancreatic cancer, contributing to 15% of cases. Traditional diagnostic approaches utilize imaging modalities like computed tomography, magnetic resonance imaging, and endoscopic ultrasound (EUS), often supported by cyst fluid analysis through fine-needle aspiration. However, these techniques exhibit limited sensitivity and specificity in identifying malignant transformation. Emerging molecular diagnostics, including analysis of carcinoembryonic antigen, glucose, IL1β, PGE2, and DNA sequencing for mutations such as KRAS and GNAS, show promise in differentiating mucinous cysts and identifying advanced dysplasia. Despite this, clinical integration remains limited. Future efforts focus on noninvasive methods, including plasma-based liquid biopsies, to complement cyst fluid analysis. A comprehensive biomarker panel integrating serum and cyst fluid markers holds the potential to improve early detection, reduce overtreatment, and optimize surgical management of high-risk PCN.
Keywords: IPMN; pancreas; pancreatic cystic neoplasms; intraductal papillary mucinous neoplasms